Label-free optical biosensor for target detection based on simulation-assisted catalyzed hairpin assembly. (February 2019) - Zhang, Yingying; Wang, Luhui; Wang, Yanan; Dong, Yafei
Graphical abstract: Taking the advantage of the high selectivity of aptamers and enzyme-free catalyzed hairpin assembly (CHA) amplification strategy, we herein describe a label-free and enzyme-free sensitive fluorescent and colorimetric strategy for amplified thrombin detection in this paper. To support both biological inquiry and technological innovation, thermodynamic models are introduced to predict the minimum energy secondary structure of interacting nucleic acid strands and calculate the partition function and equilibrium concentration for complexes in our system. Then, the thermodynamics properties of interacting DNA strands and the reactions of toehold strand displacement-driven assembly have been simulated, validating the feasibility of the theory and optimizing the follow-up lab tests. Following that, our strategy for thrombin detection is proved to be feasible and effective in biological experiments. Highlights: An algorithm has been used for analyzing the thermal performance of interacting DNA strands in our strategy. This model does not require fluorescent labeling and additional enzymes. The experiment processes and conditions are verified and optimized initially by simulations before experiments. Three experimental methods are used to verify the feasibility of the sensor. Abstract: The development of efficient and convenient strategy without involving enzyme or complex nanomaterial for the micro molecules detection has profound meaning in the diagnosis of diseases. Herein, taking the advantages of the strong affinity of aptamer and catalyzed hairpin assembly, we develop a new non-label optical amplified strategy for thrombin detection in this work. To support both biological inquiry and technological innovation, thermodynamic models are introduced to predict the minimum energy secondary structure of interacting nucleic acid strands and calculate the partition function and equilibrium concentration for complexes in our system. Then, the thermodynamics properties of interacting DNA strands and the reactions of toehold strand displacement-driven assembly have been simulated, validating the feasibility of the theory and optimizing the follow-up lab tests. Following that, our strategy for thrombin detection is proved to be feasible and effective in biological experiment. Taken together, such a biosensor has a good potential in bioactive molecules detection and disease diagnosis for future biological research.